THE RULE OF THE GHAZNAVID STATE IN MOVAROUNNAHR - Mo'ydinov Muhammadali (Journals Park Publishing, 2023)
This article discussed such issues as the establishment of the State of the Nazarenes, socio-economic relations, the country's economic life, the traditions of government, and the tax system.
Keywords: Movorounnahr, Gaza, Mahmoud Ghazal, Tajikistan, Sabuktegin, Islam, Muslim, Choganiyon.